Monthly and Diel Acoustic Occurrence of Four Baleen Whale Species in South African Waters - Fannie W. Shabangu; Kuhle Hlati; Marcel A. van denBerg; Tarron Lamont; Stephen P. Kirkman (Ecology and Evolution)
ABSTRACT Understanding of the spatio‐temporal occurrence of cetaceans post the whaling era is essential for protecting and improving management strategies of these marine mammals. To determine the monthly and diel acoustic occurrence of four baleen whale species relative to environmental conditions off the west coast of South Africa, we collected passive acoustic monitoring data within Child's Bank marine protected area in January and May through October 2024 at various water depths. Burst tonal calls of the southern African Bryde's whale offshore population were detected in January and May through July with the highest occurrence in January. Humpback whale songs and southern right whale gunshot sounds were detected from May through October with high occurrence in September and with smaller modes in other months. Antarctic minke whale bioduck calls were also found in June through October, showing high occurrence in August through October. Calls from an unknown source with similar characteristics to Antarctic minke whale bioduck calls were present in May, July, and August with the highest occurrence in August. Diel acoustic occurrence of Bryde's, southern right, Antarctic minke, and minke‐like whale calls indicated that these animals vocalised more during the day while humpback whales were more vocally active at night. Sea surface height and sea surface temperature, either separately or in combination, were the most important predictors of whale acoustic occurrence, highlighting the influence of environmental conditions on the distribution, habitat selection, and ecology of these whales. Overall, this study advances our understanding of the movement, occurrence, and behavioural patterns of several baleen whales relative to environmental conditions. It also provides the first description of the southern African Bryde's whale offshore population's call characteristics, which will be useful at guiding future studies to acoustically differentiate between it and the inshore population.